Identification and AmpC beta-lactamase analysis of Enterobacter spp. isolated from clinical sources / Fatin Izzati Mohd Khari - Fatin Izzati, Mohd Khari (2017)
Enterobacter spp. have been recognized as major nosocomial pathogens associated with high occurrence of cephalosporin resistance in many parts of the world. The objectives of this study were to speciate Enterobacter spp. isolated from various clinical sources in the University Malaya Medical Centre, Malaysia (from November 2012-February 2014), and to determine AmpC -lactamase (AmpC) production of these isolates. In this study, 117 isolates previously identified as Enterobacter spp. (either by in-house biochemical tests or Vitek2) were subjected to identification using API 20E system identification system (bioMérieux, Marcy l’Etoile, France) and Matrix-assisted laser desorption ionization-time of flight mass spectrometry analysis (MALDI-TOF MS, Bruker Daltonics, Bremen, Germany). MALDI-TOF MS analysis revealed the identification of Enterobacter cloacae (n=76), Enterobacter aerogenes (n=27), Enterobacter asburiae (n=12) and Pluralibacter gergoviae (n=2). A total of 25 (21.4%) isolates were discrepantly identified by MALDI-TOF MS and API 20E system. Further analyses of hsp60 and rpoB partial gene sequences confirmed the identification by MALDI-TOF MS analysis for 23 of the 25 discordant isolates when identifying to Enterobacter to the species/complex level. Approximately 40.0% Enterobacter isolates investigated in this study were resistant to cefotaxime and ceftriaxone, while 23.9% isolates were resistant to ceftazidime. A total of 111 (94.9%) of the 117 Enterobacter isolates in this study were potential AmpC producers, based on the finding from cefoxitin disk screening test. AmpC production was detected in 99 (89.2%) of the 111 isolates using D69C AmpC Detection Set (MASTDISC™ID). The detection rates for AmpC production were lower using cefoxitin-cloxacillin double disk synergy test (80.2%) and AmpC induction test (50.5%). Low agreement was observed between D69C AmpC detection set and these two phenotypic tests. Using a multiplex PCR assay for plasmid-mediated AmpC detection, chromosomal AmpC gene (MIR/ACT) was detected in 36 (47.4%) v isolates of E. cloacae and three isolates of E. asburiae, while a plasmid-mediated AmpC gene (DHA-type) was detected from a urine isolate of E. cloacae. The association of AmpC production with mutations in ampD and ampR gene regions of three cefoxitinsensitive and 13 potential AmpC producers of E. cloacae were investigated in this study. A number of amino acid changes in ampD (E4K, P62S, F63Y, H69N, E131Q, I141V and R143L) and ampR (T106I, E114D, G149S, A175T, S179C, P208S, I259V, and E274K) genes were identified, however no specific correlation was noted between the mutations and AmpC production of the isolates. PFGE analysis showed the differentiation of Enterobacter isolates into 80 pulsotypes, however no specific association was noted between pulsotypes and Enterobacter species or specimen type. The sharing of pulsotypes among E. cloacae isolates, suggests the existence of more than one clone of E. cloacae amongst the isolates investigated in this study. In conclusion, the finding in this study shows the ability of MALDI-TOF MS method in providing rapid and accurate identification of Enterobacter species. This study presents an update on the speciation of Malaysian isolates of Enterobacter spp. and phenotypic and genotypic determination of AmpC production in our isolates. Surveillance and infection control measures are essential to limit the spread of these organisms in the hospital.